2019
DOI: 10.1108/jabs-07-2018-0193
|View full text |Cite
|
Sign up to set email alerts
|

Innovative product marketing strategy: multinational companies in Bangladesh

Abstract: Purpose This paper aims to deal with international marketing of products, analyzing how adaptation/standardization and network development are achieved when marketing products in Bangladesh. Design/methodology/approach By applying a qualitative method, the study was conducted at four multinationals, British American Tobacco, Perfetti Van Melle, Tetrapak and Reckitt Benckiser, operating in Bangladesh. Data were collected through semistructured interviews, direct observation and official documents. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…His research showed that the cultural and market environment can standardize the quality of the product and make the marketing components meet the needs of consumers. He contributed marketing literature based on context, trust, network, and adaptive product marketing model [1].…”
Section: Related Workmentioning
confidence: 99%
“…His research showed that the cultural and market environment can standardize the quality of the product and make the marketing components meet the needs of consumers. He contributed marketing literature based on context, trust, network, and adaptive product marketing model [1].…”
Section: Related Workmentioning
confidence: 99%
“…This required international or global brands to use the local power to be accepted in the market [1]. In other words, it is necessary to fully adapt to the consumers' preferences [19] in the region an international brand does business with. Although many books and chapters that we came across suggested adaptation as the main key to enter the global market.…”
Section: Sustainability's Challenge 3: Marketing Activities In International Businessmentioning
confidence: 99%
“…Thus, going international or global is a true challenge that may lead to a very quick failure [22]. However, all constraints are being observed and given directions [1,[19][20][21][22][23] how an international/global brand should behave to succeed in the global arena. In every business attempt, international businesses will use either adapt or standardize [24].…”
Section: Sustainability's Challenge 3: Marketing Activities In International Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Dewasiri et al (2021) discuss the importance of understanding cultural dynamism and consider j JOURNAL OF ASIA BUSINESS STUDIES j differences between cultures to develop a successful IM strategy. The laws, regulations and rules in the host country also influence the business environment for an international firm and the IM strategy of a firm (Fregidou-Malama et al, 2019). The literature shows that relationships between stakeholders are affected by social norms and the culture distance between them, and connections are necessary for the development of networking across countries (Narooz and Child, 2017).…”
Section: Definitions Of Institutional and Cultural Contextmentioning
confidence: 99%